A case report of steroid-refractory bullous pemphigoid induced by immune checkpoint inhibitor therapy - Guan, Shasha; Zhang, Linlin; Zhang, Junyan; Song, Wenjing; Zhong, Diansheng (Frontiers in Immunology, 2023)
The widespread use of immune checkpoint inhibitors in several malignancies has revealed new immune-related adverse events. Bullous pemphigoid (BP) is an antibody-driven autoimmune disease characterized by skin inflammation and fluid-filled bullae. Herein, a 69-year-old man with lung squamous cell carcinoma developed multiple vesicles and tense bullae 3 weeks after the initiation of a programmed death-1 (PD-1) inhibitor, pembrolizumab, and chemotherapy. Biopsy revealed a subepidermal bulla with lymphocytic and eosinophil infiltration, and immunohistochemical studies predominantly showed CD4+ cells, a few CD8+ cells, and the occasional CD20+ lymphocyte. The serum anti-BP180 antibody level, as well as the interleukin-6 (IL6) and interleukin-10 (IL10) levels, were elevated compared to the lower levels of tumor necrosis factor-α (TNF-α). Eosinophil levels were high and consistent with the development of blisters. A diagnosis of BP associated with PD-1 inhibitor therapy was made, and the Common Terminology Criteria for Adverse Events (CTCAE) classification was grade 3. Immunotherapy was permanently discontinued, and the patient’s bullous lesions failed to react to high-dose systemic corticosteroids combined with minocycline and niacinamide. Intermittent blister recurrence occurred in 2 months, eventually improving with the administration of two courses of intravenous immunoglobulin (IVIG). At 5 weeks of follow-up, the patient’s tumor was reduced on a computed tomographic scan. Despite stable BP treatment, the patient repeatedly developed complications due to the complexity of the underlying disease and could not be treated with anti-tumor therapy. Early recognition and management of serious immune-related bullous dermatologic toxicity are essential for patient safety.